Pengaruh Lingkungan Kerja Dan Budaya Organisasi Terhadap Kepuasan Kerja Pegawai Pada Dinas Komunikasi Informatika Dan Statistik Kabupaten Bima - Sadaqah (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2021)
This study aims to determine and analyze the influence of the work environment and organizational culture on employee job satisfaction at the Department of Communication, Information and Statistics, Bima Regency. This type of research is associative by using a Likert scale questionnaire research instrument. The population used is all employees who work at the Department of Communication, Informatics and Statistics, Bima Regency as many as 52 people, consisting of 37 civil servants, 10 volunteer employees and 5 contract employees. The sample in this study were 37 employees at the Department of Communication, Informatics and Statistics, Bima Regency with the status of civil servants (PNS) with saturated sampling technique. Methods of data collection using observation, interviews, questionnaires and literature study. The data analysis technique used is validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation coefficient, determination test, t test and f test. The results showed that the work environment and organizational culture had a significant effect on employee job satisfaction at the Department of Communication, Informatics and Statistics, Bima Regency with a very strong relationship level of 93.4%.